2005
DOI: 10.1016/j.yexcr.2005.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Jun N-terminal kinase (JNK) pathway by HSV-1 immediate early protein ICP0

Abstract: The immediate early protein ICP0 encoded by herpes simplex virus 1 (HSV-1) is believed to activate transcription and consequently productive infection. The precise mechanisms of ICP0-mediated transactivation are under intensive study. Here, we demonstrate that ICP0 can strongly activate AP-1 responsive genes specifically. This activation is inhibited by c-Jun (S73A), c-Jun (S63/73A), TAK1 (K63W), but not by p38 (AF), ERK1 (K71R), ERK2 (K52R) and TRAF6 (C85A/H87A). We further investigate the relevancy of ERK, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…At high MOIs, viral replication appears to circumvent the requirements of ICP0, because under these conditions, replication is not dependent on ICP0 (67). A previous study reported that HSV-1 ICP0 interacts specifically with transforming growth factor-activated protein kinase 1 and stimulates c-Jun N-terminal kinase activity but has no effect on ERK activity (19). Our results are consistent with this report; tankyrase 1 was not phosphorylated in ICP0-overexpressing cells.…”
Section: Discussionsupporting
confidence: 92%
“…At high MOIs, viral replication appears to circumvent the requirements of ICP0, because under these conditions, replication is not dependent on ICP0 (67). A previous study reported that HSV-1 ICP0 interacts specifically with transforming growth factor-activated protein kinase 1 and stimulates c-Jun N-terminal kinase activity but has no effect on ERK activity (19). Our results are consistent with this report; tankyrase 1 was not phosphorylated in ICP0-overexpressing cells.…”
Section: Discussionsupporting
confidence: 92%
“…Under these circumstances, JNK activation may influence important cellular consequences, such as alterations in gene expression (1,53,59,162,167,176,199,294,325,326,346), cell death (58,89,137,139,169,193,243,293), viral replication, persistent infection or progeny release (215,224,251,260), or altered cellular proliferation (178). The exact mechanism of JNK activation under each of these circumstances remains to be elucidated fully, although there may be involvement of Toll-like receptors, direct pathway modulation through interaction with upstream protein regulators, or the activation following an ER stress response (79,87,110,124,143,191,253,261,279,294,312).…”
Section: Fig 1 Overview Of the Jnk Pathway (A)mentioning
confidence: 99%
“…Plasmids of human JNK1, JNK2,  and JNK1 (APF) were kindly provided by Professor Lin Li (Shanghai Institute of Biochemistry and Cell Biology, Shanghai, China). cDNAs encoding TAK1, TAK1 (KD), TAB1, IKKb, and the reporter genes (5× kB-Luc and pRL-SV40) have been described previously [56]. The (PRDIII-I)4-Luc reporter gene construct was kindly provided by Professor Stephan Ludwig (Heinrich-Heine-University, Duesseldorf, Germany).…”
Section: Plasmidsmentioning
confidence: 99%